Literature Review: Effect of Exposure to Weapon Tear Gases CN, CS, and OC on Toxicity - Setyanjana, Andre Yoan (Proceeding International Conference on Religion, Science and Education, 2024)
Tear gas is a mixture of chemicals used for crowd control without the use of lethal weapons. Tear gas or also called lacrimator was first used during World War I which was categorised as a chemical weapon. The chemicals contained in tear gas include CS gas (o-chlorobenzylidene malonitrile), CN gas (2-chloroacetophenone), and pepper spray (OC gas, oleoresin capsicum). This research is a literature review. The use of databases in searching for articles using Google Scholar, DOAJ, and Science Direct with the keywords "Tear gas, CN, CS, OC, and Toxicity" conducted by previous studies both at home and abroad. The results of the literature review obtained some toxicity data caused by tear gas exposure which has an impact on toxicity and health. CN, CS and OC are effective lacrimating agents, the evidence of toxicity as measured by threshold time for irritation, is greatest for CN, followed by CS and OC. Typically, eye and respiratory tract irritation occurs within 20-60 seconds of exposure. Tear gas works by irritating the mucous membranes of the eyes, nose, mouth, skin and lungs. This compound causes tears (crying), and hence the gas is called tear gas. Exposure to tear gas causes short-term and long-term effects, including respiratory illness, eye disease, skin inflammation, and damage to the circulatory and digestive systems. The gas also causes sneezing, coughing, breathing difficulties, eye pain, temporary blindness, and fatality.